PELLET PRODUCTION MACHINE DESIGN USING THE AXIOMATIC HOUSE OF QUALITY (AHOQ) METHOD AT NABOLAK FISHERY - Saragi, Hadi Sutanto; Sihaloho, Iswanti; Mauliate, Isak; M., Wesly (Jurnal Ilmiah Teknik Industri, 2024)
In fish farming, the most significant operational cost is the cost of feed or pellets. Nabolak Fisheries is one of the fish farms in Toba Regency. Nabolak Fisheries can process fish harvests directly into packaged derivative products such as fish meat processed into nuggets, fish bones processed into crackers, and dregs from processing residues used as catfish feed. Nabolak fisheries have the potential to produce fish pellets to reduce operational costs and increase revenue. With their own pellet production machine, fish farmers in the Nabolak Fishery can produce their feed and add derivative products. The design of pellet production machines that are effective, efficient, and follow the needs of fish farmers in order to increase farmer productivity. The Axiomatic House of Quality (AHOQ) method is an effective method for solving pellet machine design problems. This method determines what machine specifications are needed by involving customer requirements, functional requirements, and other elements. After obtaining the design and specifications, modeling was carried out using Solidwork software. Solidwork will feature a three-dimensional design. The three-dimensional design produced by SolidWorks is then given to the blacksmith to make the pellet production machine.